Sufi Orders in the Colonial Era: An Analysis of Their Urgency and Impact - Hidayat, Asep Achmad; Savitri, Alfa Dini (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2025)
There are several important points in this paper, including: the role of the tarekat in the spread and development of Islam in the Dutch East Indies, the reaction of the indigenous people to the emergence of the tarekat in the Dutch East Indies and the response of the Dutch colonial government to the tarekat which became the driving force towards independence. This study applies the library research method with a historical approach. Based on the results of the analysis carried out, the researcher concluded that the tarekat during the colonial period had a fairly important place and role for the indigenous people and elites, because it was not only a space for the spread and development of Islam in the Dutch East Indies but in this period the tarekat succeeded in suppressing the hegemony of the colonial government and became the driving force for Indonesian independence.